Keeping the driver in the loop: Dynamic feedback to support appropriate use of imperfect vehicle control automation. Issue 125 (May 2019) - Seppelt, Bobbie D.; Lee, John D.
Highlights: Continuous feedback on the state and behavior of automation that informs operators of the evolving relationship between system performance and operating limits, designed with appropriate attention to visual and cognitive costs, is able to promote proactive operator responses to automation failures and accurate mental models of system processes. Modality and feature complexity are key design decisions of continuous feedback that govern resulting visual and cognitive costs associated with use of these displays while driving. In-vehicle automated systems should be designed to inform instead of alert drivers to automation failures. Abstract: Objective: This study evaluates the benefits and costs associated with providing drivers continuous feedback on the limits and behavior of imperfect vehicle control automation. Background: In-vehicle automated systems remove drivers from active vehicle control, often at the expense of timely interventions when failures occur. Discrete warnings, as a type of feedback to inform drivers about automated system behavior, fail to keep drivers aware of its proximity to operating limits. Method: In a fixed-based simulator, 48 drivers drove using Adaptive Cruise Control (ACC)—a form of control automation that maintains a set speed, or a set headway if the vehicle encounters a slower moving vehicle. A first experiment compared ACC with discrete warnings to ACC with continuous information, which indicated moment-to-moment ACC state relative to its operating limits. Three display conditions, designed to provide non-obtrusive, ecologically-valid information, were evaluated in a second experiment: 1) a visual interface; 2) an auditory interface; and 3) a combined visual-auditory interface. Results: Drivers provided with continuous feedback relied more appropriately on ACC than did those with discrete warnings. Continuous feedback increased the frequency of proactive responses to automation failures and improved system understanding. Of the three displays, the combined visual-auditory interface performed the best. Conclusion: Continuous feedback helped communicate to drivers the evolving relationship between system performance and operating limits. Application: Displays for increasingly automated vehicles should inform about the automation's situation-specific behavior rather than simply alert drivers to failures and/or the need to resume vehicle control in order to promote appropriate understanding and trust.